Continuous miniemulsification for the industrialization of miniemulsion polymerization - Goikoetxea, Monika (2011)
Miniemulsion polymerization allows the synthesis of a broad range of materials, which are not obtainable by means of other polymerization processes in dispersed media such as conventional emulsion polymerization. However, the industrial implementation of the miniemulsion polymerization is being hindered by the miniemulsification process, which may require long times leading to unacceptable process times. This work explores the feasibility of using a continuous miniemulsification system that includes a static mixer and a high pressure homogenizer in series, in both loop arrangement and single pass. The proposed system allows the production at high rates, of high solids content miniemulsions containing a very viscous organic phase.